2000
DOI: 10.1002/(sici)1521-3757(20000204)112:3<617::aid-ange617>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Morphosynthese von Bariumsulfat-Kristallen mit Hilfe von doppelhydrophilen Blockcopolymeren

Abstract: Nanofasern, Pfirsich‐, Erdnuss‐ und Blumen‐artige Strukturen (siehe Bild) entstehen beim Fällen einfacher Mineralien in Gegenwart spezifisch adsorbierender Polymere. Dies wird am Beispiel von BaSO4 und doppelhydrophilen Blockcopolymeren, die Carbon‐, Sulfon‐, Phosphon‐ oder Asparaginsäure‐Einheiten enthalten, illustriert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Recently, increasing evidence was found that biomineralization takes place through amorphous precursor particles, for example, as reported for sea urchin spines. [10,11] Revisiting the existing literature shows indeed that comparable observations have been made in synthetic inorganic chemistry much earlier, even in the absence of additives, [12,13] and the question can be raised if precursor particles and their superstructures also play a role-at least as intermediatesin crystallization in a much broader context. Further advantages of this crystallization pathway are highly efficient mass fluxes that are independent of solubility-products, the coupled high crystallization speeds, and crystallization without change of the pH value and the osmotic pressure.…”
Section: Introductionmentioning
confidence: 73%
“…Recently, increasing evidence was found that biomineralization takes place through amorphous precursor particles, for example, as reported for sea urchin spines. [10,11] Revisiting the existing literature shows indeed that comparable observations have been made in synthetic inorganic chemistry much earlier, even in the absence of additives, [12,13] and the question can be raised if precursor particles and their superstructures also play a role-at least as intermediatesin crystallization in a much broader context. Further advantages of this crystallization pathway are highly efficient mass fluxes that are independent of solubility-products, the coupled high crystallization speeds, and crystallization without change of the pH value and the osmotic pressure.…”
Section: Introductionmentioning
confidence: 73%
“…For example, similar to biomineralization, inclusions of additives up to 30 wt % are observed in synthetically grown crystals, too. [10,11] Revisiting the existing literature shows indeed that comparable obser vations have been made in synthetic inorganic chemistry much earlier, even in the absence of additives, [12,13] and the question can be raised if precursor particles and their superstructures also play a role at least as intermediates in crystallization in a much broader context.…”
Section: Introductionmentioning
confidence: 83%
“…of numerous applications such as mineral separation [4], flocculation [5,6] or retention [7]. In the field of biology the growth of biominerals, that is believed to be determined by specific interactions between biopolymers and the mineral surface, is just one example of a process that is mediated by polymer adsorption [8][9][10][11]. Due to its widespread occurrence and importance polyelectrolyte adsorption is the focus of interest for experimental research [12][13][14][15][16][17][18][19][20][21][22] as well as for theoretical considerations [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%